Israel/Palestine in World Religions - Troen, S. Ilan. author. aut Link
XVII, 250 p.
Keywords: “This is one of the most important books on Israel and Palestine to appear in some time” —Alan Dowty, University of Notre Dame, Past President, Association for Israel Studies, author of Israel/Palestine “One of the leading figures in the field of Israel Studies, Ilan Troen demonstrates the vast range of Jewish, Christian, and Islamic theological claims and their impact on our supposedly secular political debates. Sensitive to both religious and political interests, Troen brings a new depth of understanding to the conflict.” —Susannah Heschel, Eli M. Black Distinguished Professor, Dartmouth College “An important, accessible, and much needed contribution toward understanding the many entangled factors that make the conflicts in the Middle East so intractable.” —Philip A. Cunningham, Professor of Theology, President of the International Council of Christians and Jews, Saint Joseph's University, Philadelphia The struggle over Israel/Palestine is not just another contest by competing nationalisms or an instance of geopolitical competition. It is also about control of sacred territory that involves local Jews, Muslims, and Christians as well as worldwide faith communities, each with their own interests and stake in what transpires. This balanced introduction to a complex subject presents the multiple positions within the great monotheistic traditions. It demonstrates that the secular discourses in the public square concerning ownership privileges, historical precedence, political rights, and justice that have allegedly replaced religious claims actually coexist with, and often complement, the theological. It explores the century-long tangle of secular and theological debates about Israel’s legitimacy. Whether readers support a Jewish state or are resolutely opposed, the serious and substantial scholarship of this well-reasoned and innovative book will contribute to a nuanced and better-informed understanding of this persistent issue that has entered its second century on the international agenda. S. Ilan Troen is Lopin Professor of Modern History Emeritus at Ben-Gurion University, Israel, Stoll Family Professor in Israel Studies Emeritus at Brandeis University, USA, and founding director of the Israel Studies centers at both institutions. He is Founding Editor of the journal Israel Studies, and 2023 recipient of the Association for Israel Studies “Lifetime Achievement Award.”.